On the Creative Process: The Ephemerality of Silence of the World. Issue 4 (December 2021) - Duarte, Andreia; Spinelli, Miro
Abstract : The scenic experiment Silence of the World brought together indigenous leader Ailton Krenak and performer Andreia Duarte. The show deeply explored the perception of time in mythology as a space for reinventing the world and evoked the recognition of humans as just another planetary species alongside so-called nonhumans: animals, rivers, mountains, plants, and everything that exists. Silence of the World drew attention to indigenous peoples who connect with the living organism that is the planet.